Is ‘digital transition’ a syntax error? Purpose, emergence and directionality in a contemporary governance discourse - Bonno Pel (Journal of Responsible Innovation)
An important precondition for responsible innovation is the awareness of directionality: Dynamic innovation processes can take different, more or less favorable, turns. The ongoing wave of digital innovations exemplifies how this directionality challenges societal actors to develop new strategic dispositions. This paper critically examines the ‘digital transition’ as a rather paradoxical ‘knowing of governance’. It appears to refer simultaneously to digital instruments and directed automated futures and to rather spontaneously occurring digitalization. The analysis explores this apparent ‘syntax error’ through academic scholarship, gray literature, as well as newspaper sources. Critical discourse analysis demonstrates how directionality is obscured through various ideological representations of directed transitions but also disclosed through an increasingly rich vocabulary on emergent digitalization issues. Calling attention to the partly purposive, partly emergent nature of the transformation process, the ‘digital transition’ notion can help to express directionality.